A hare-raising tail - Levy, Elizabeth, 1942-; Gerstein, Mordicai (New York, NY : Scholastic Inc., 2002)
After Fletcher, a salami-loving basset hound, is wrongly accused of eating a pet rabbit, he and his sidekick, Jasper the flea, must find the true culprit before Fletcher is sent back to the dog pound.
G2
Keywords: Basset hound -- Fiction; Dogs -- Fiction; Fleas -- Fiction; Rabbits -- Fiction; Schools -- Fiction; Humorous stories; Mystery and detective stories